PERILAKU ORGANISASI DALAM PELAYANAN PUBLIK (STUDI PADA APARATUR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA AMBON) - CHYNTHIA IMELDA TJOKRO (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2019)
Organizational behavior indicates the individual characteristics of interacting with the environment. This research aims to determine how the organization’s behaviour in public service is held in the Civil Registration office of Ambon. The method used is a qualitative descriptive method of study with data retrieval techniques is observation and interviews.The results showed that the organization’s behaviour relating to public service in the population and civil registration service in the city of Ambon still needs to be repaired both the system and its human resources so that the satisfaction of the apparatus can be the benchmark performance assessment of population service apparatus and civil registration of Ambon.